2023
DOI: 10.1177/23312165221141142
|View full text |Cite
|
Sign up to set email alerts
|

Musical Emotion Categorization with Vocoders of Varying Temporal and Spectral Content

Abstract: While previous research investigating music emotion perception of cochlear implant (CI) users observed that temporal cues informing tempo largely convey emotional arousal (relaxing/stimulating), it remains unclear how other properties of the temporal content may contribute to the transmission of arousal features. Moreover, while detailed spectral information related to pitch and harmony in music — often not well perceived by CI users— reportedly conveys emotional valence (positive, negative), it remains unclea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 73 publications
3
17
0
Order By: Relevance
“…With respect to categories, joy was categorized with the most sensitivity and sadness with the least. This is in line with the overall sensitivity reported with NH participants with the vocoded version of the current musical emotion stimuli (Harding et al, 2023). This finding generally aligns with visual inspection of accuracy scores in Ambert-Dahan et al (2015) (d' and mean scores not reported), where CI users categorized musical emotion in classical excerpts with four emotions: happiness, fear, sadness and peacefulness.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…With respect to categories, joy was categorized with the most sensitivity and sadness with the least. This is in line with the overall sensitivity reported with NH participants with the vocoded version of the current musical emotion stimuli (Harding et al, 2023). This finding generally aligns with visual inspection of accuracy scores in Ambert-Dahan et al (2015) (d' and mean scores not reported), where CI users categorized musical emotion in classical excerpts with four emotions: happiness, fear, sadness and peacefulness.…”
Section: Discussionsupporting
confidence: 91%
“…The findings replicated the results with NH participants tested with vocoders in a previous study (Harding et al, 2023). The d’ range of current adult CI users was similar to the d’ range of vocoded excerpts reported by Harding et al (2023) and below that of the d’ scores with the fully presented, non-vocoded acoustic signal.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations